Evaluation of Service Quality Gaps in Pos Express Services Using the SERVQUAL Method - Muhamad Alif Fitrah Adriansyah; Rahayu Amalia; Ari Muzakir (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study aims to analyze the service quality of Pos Express in South Sumatra by applying the SERVQUAL method to identify gaps between customer expectations and perceptions. A quantitative approach was employed by distributing structured questionnaires to 120 respondents selected through purposive sampling. The measurement instrument was developed based on five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The results indicate that customer expectations were consistently higher than perceived service performance across all dimensions. The largest negative gap values were found in the responsiveness (-0.73) and reliability (-0.72) dimensions, indicating weaknesses in service response time, complaint handling, delivery punctuality, and information accuracy. Meanwhile, the empathy dimension recorded the smallest gap (-0.29), suggesting relatively positive interpersonal interactions between staff and customers. To support data processing and analysis, a web-based evaluation system was developed to automate SERVQUAL calculations and reporting. The system facilitated efficient data management and improved the accuracy of service quality analysis. Overall, the findings highlight the need for service improvement, particularly in enhancing operational reliability and responsiveness. This study provides empirical evidence to support service quality management and decision-making in regional postal services.